Psychometric properties of Farsi version of the resilience scale (CD-RISC) and its role in predicting aggression among Iranian athletic adolescent girls - Roghieh Nooripour; Simin Hoseinian; Yaghoob Vakili; Nikzad Ghanbari; Joshua J. Matacotta; Nazir Mozaffari; Hossein Ilanloo; Carl Lavie (BMC Psychology, 2022)
Abstract The sport presents an opportunity for young people to experience the joys of success and cope with setbacks to develop resilient behaviors. However, there is a lack of clarity about how sport can cultivate resilience, particularly among adolescent girls. This study investigated the psychometric properties of Farsi version of the Resilience Scale (CD-RISC) and its role in predicting aggression in Iranian athletic adolescent girls. The method of the present study was cross-sectional. The population of this study was Iranian athletic adolescent girls, and 475 Iranian athletic adolescent girls were selected through the convenience sampling method. The participants completed the Resilience Scale (CD-RISC), Quality of Mindfulness, General Self-efficacy (GSE), Alexithymia, and Aggression Scale. The CD-RISC’s psychometric properties were analyzed using confirmatory factor analysis, while reliability was tested using Cronbach’s alpha. Discriminant validity was measured by examining the relationship with alexithymia, and convergent validity was assessed with the quality of mindfulness and GSE. In addition, multiple regression analysis was conducted on the prediction of aggression by the CD-RISC subscales. The five-factor structure provided a good fit for the data. CD-RISC had significant negative associations with alexithymia, and there was a significant positive correlation between CD-RISC and Quality of Mindfulness, GSE. The results indicate that CD-RISC significantly predicts aggression in athletic adolescent girls. The CD-RISC has good validity for athletic adolescent girls in Iran and can be used in psychological evaluations in the Iranian context. CD-RISC significantly predicts aggression among athletic adolescent girls.